2010
DOI: 10.1021/bi9017208
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of Lipoprotein−Receptor Interactions: Properties of Ligand Binding Modules Governing Interactions with Apolipoprotein E

Abstract: Clusters of complement-type ligand binding repeats in the LDL receptor family are thought to mediate the interactions between these receptors and their various ligands. Apolipoprotein E, a key ligand for cholesterol homeostasis, has been shown to interact with LDLR, LRP and VLDLR, through these clusters. LDLR and VLDLR each contain a single ligand-binding repeat cluster, whereas LRP contains three large clusters of ligand binding repeats, each with ligand binding functions. We show that within sLRP3, the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 58 publications
4
72
0
Order By: Relevance
“…Analysis of the binding isotherm with an N-identical binding sites model showed that rHP14-LA bound calcium with an apparent affinity of K D ∼ 3 μM, and thermodynamic parameters of ΔH = −18 kcal/mol, and ΔS = −34.3 cal/mol deg. These values are comparable to those obtained for LAs (CR17 and 18) from the human LDLR family (20). The calcium concentration in hemolymph is ∼5 mM (21) and, thus, likely sufficient to saturate HP14 LAs.…”
Section: Resultssupporting
confidence: 78%
“…Analysis of the binding isotherm with an N-identical binding sites model showed that rHP14-LA bound calcium with an apparent affinity of K D ∼ 3 μM, and thermodynamic parameters of ΔH = −18 kcal/mol, and ΔS = −34.3 cal/mol deg. These values are comparable to those obtained for LAs (CR17 and 18) from the human LDLR family (20). The calcium concentration in hemolymph is ∼5 mM (21) and, thus, likely sufficient to saturate HP14 LAs.…”
Section: Resultssupporting
confidence: 78%
“…Indeed, the cluster's binding site for ApoE is presented by a CR triplet (CR.16-18), and the strongest binding CR doublet (CR.17-18) to a relevant ApoE peptide was 10-fold weaker than with the triplet. 47 At the same time, the RAP binding can be relevant to both models. In support for the first model, such binding was proposed to involve simultaneously up to six adjacent CRs of a receptor 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The ligands bind to the receptor using side chains from a lysine and a hydrophobic residue (37)(38)(39)(40). This simple motif has been identified in many complexes between ligands and CR-domains, including a minor group of human rhinovirus and three CR-domains from the very low density lipoprotein receptor (41), Reelin, in complex with two CR-domains from the apolipoprotein E receptor 2 (42, 43), ␤2-microglobulin in complex with the fourth CR-domain from LDLR (44,45), and apolipoprotein E with CR17 from LRP1 (46,47). These protein complexes represent classical extracellular ligands binding to endocytosis receptors; dissociation of the complex in the acidic endosome allows degradation of the ligands upon further transport to the lysosome and recycling of the receptors to the cell surface (48).…”
Section: App Binding To Sorla Under Acidic Conditions Is Linked To Unmentioning
confidence: 99%